Measurements of the electron and muon inclusive cross-sections in proton-proton collisions at √s=7TeV with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdelalim, A; Abdesselam, A; Abdinov, O; Abi, B; Abolins, M; Abramowicz, H; Abreu, H; Acerbi, E; Acharya, B; et al. (2012)
This Letter presents measurements of the differential cross-sections for inclusive electron and muon production in proton-proton collisions at a centre-of-mass energy of s=7TeV, using data collected by the ATLAS detector at the LHC. The muon cross-section is measured as a function of pT in the range 4